Parity theorems revisited: an ARDL bound test with non-parity factors - Syed Mohamed, Mohamed Ariff; Zarei, Alireza (Asian Academy of Management (AAM) and Penerbit Universiti Sains Malaysia, 2015)
The research question addressed in this paper is, do inflation and interest rate differences across two major economies fully drive the long-run exchange rate changes if controls for non-parity factors are embedded? Exchange rate behaviour research is once again an interesting topic given the availability of powerful econometric approaches to resolve unsolved issues. We re-examine the exchange rate behaviour of the US economy, applying a more appropriate econometric model using 55 years of quarterly data. The model explains 96% of variation in exchange rates, which testifies to the model’s appropriateness. The error correction estimate indicates a time-to-equilibrium of 0.139 per quarter; that is, full adjustment takes seven quarters. Tests indicate evidence of a long-run relationship among the exchange rate, prices, and interest rates. The coefficients on both parity factors (prices and interest rates) are statistically significant with correct theory-suggested signs. These findings constitute strong evidence in support of parity and non-parity theorems while confirming that the US currency behaviour over 1960–2014 is consistent with parity and non-parity theories.